Requiem for a sacrifice: Mourning narratives of the Tamil Tigers’ defeat - Mantovan, G. (2022)
The Liberation Tigers of Tamil Eelam (LTTE) were defeated in 2009 after three decades of fighting for the independence of the Tamil minority in Sri Lanka. Unwilling to surrender even when defeat looked certain, the LTTE fighters, taking many civilians with them, retreated for four months as the Sri Lankan army gradually surrounded them and slaughtered thousands of fighters and civilians. What is the meaning of the defeat for those fighters who have survived the carnage? What have been the effects of the defeat? How do the LTTE survivors remember this event in exile? The proposed analysis is based on ethnographic fieldwork on Tamil narratives of the Sri Lankan civil war, conducted in Paris between 2009 and 2019. Through an analysis of the LTTE fighters’ description of the defeat, and of their imaginaries, this article aims to understand how the members of a nationalist revolutionary group experienced the annihilation of their organisation. This analysis will show that defeat is associated with deep anthropological issues that are worth exploring: far from being only a military or political matter, defeat has a profound cultural and social impact both on how the vanquished remember the tragic past and on how they deal with the new post-war situation. For the former fighters, the LTTE’s destruction was not only a military and humanitarian catastrophe, but also spelt the end of a way of being and of a social organisation. In their testimonies, the fighters describe the fall of their organisation in the last months of the war. They lost everything, even basic things like shelter, food and the right to cremate or bury their dead and to treat the wounded. Nevertheless, they emphasise that they fought to the bitter end and never thought of leaving or surrendering. Based as it was on the idea of sacrifice in the name of the struggle for independence, the imaginary of the LTTE ruled out the possibility of surrender—their way of thinking revolved around the dichotomy between victory or death. Indeed, according to the survivors, many fighters and especially the leaders chose to commit suicide rather than surrender to the enemy. The article also analyses how the defeat and the LTTE’s imaginary and ideology have impacted the fighters’ lives in exile and their relationship with others (i.e. the Sri Lankan state and the Tamil diaspora, particularly nationalist associations). The LTTE’s imaginary and ideology have profoundly influenced the fighters’ efforts to build themselves a new life as defeated survivors—the fighters continue to think of themselves according to the old categories of the LTTE. Thus, though most of them now lead a decent life in France (they have a job and often enjoy refugee status), they experience the condition of defeat as a silent solitude, an incapability of finding a third way beyond the victory–defeat dichotomy. This article seeks to contribute to the study of defeat and vanquished people, a neglected topic in anthropology and the social sciences. It has been argued that any major defeat will change a political regime, a people’s behaviour, and their forms of political participation (Dower, 1999; Hashimoto, 2015). An event of this sort constitutes an opportunity to critically rethink one’s own history and the “intellectual order” of one’s country (Bloch, 2006; Koselleck, 2005). However, for the LTTE fighters, defeat concerned all aspects of their world: what has been defeated as a result is a whole world-view. In other words, defeat is a loss. The LTTE fighters, unable to reinvent themselves without the organisation, still need the Tigers in order to think about themselves and find an identity. For them, to be defeated is to be still attached to what they have lost even though the world is changing. The article ends by inviting further research on this topic, also including non-activists. Moreover, it underlines that defeat is never fixed in time: though a particular defeat may be clearly defined in terms of its occurrence and consequences, its interpretations and memories may change over time and across different social groups.